Analisis Waktu dan Biaya Proyek Pembangunan Gudang Ketahanan Pangan Polri di Polda Gorontalo Menggunakan Metode Earned Value Analysis - Riski S. Siko; Arfan Usman Sumaga; Arfan Utiarahman (Transbahasa, 2026)
Time and cost control are essential factors in ensuring the successful execution of construction projects. This study aims to compare project performance with the initial plan and evaluate the remaining time and cost required to complete the project. The Earned Value Analysis method was applied to analyze the project performance indices, allowing the assessment of cost efficiency, schedule efficiency, and the estimated time and cost required for project completion. The object of this study is the Food Security Warehouse Construction Project of the Indonesian National Police at Gorontalo Regional Police. The analysis was carried out using S-curve data, planned progress, and actual project cost realization. The analysis results show that from week 1 to week 17, the BCWP value is consistently higher than the BCWS value, indicating that the project progress is ahead of schedule (SPI > 1). This condition is reinforced by the ACWP value being lower than BCWP, as well as positive CV and SV values with CPI and SPI > 1, which demonstrates that cost and schedule control have been managed effectively and efficiently. Based on the estimation results, the project can be completed on time, cost-efficiently, and 100% without requiring additional budget, thus remaining within the initial budget limit of Rp5,180,854,000.